Position-Based Virtual Fixtures for Membrane Peeling with a Handheld Micromanipulator - Becker, Brian C. (2012)
Peeling delicate retinal membranes, which are often less than 5 µm thick, is one of the most challenging retinal surgeries. Preventing rips and tears caused by tremor and excessive force can decrease injury and reduce the need for follow up surgeries. We propose the use of a fully handheld microsurgical robot to suppress tremor while enforcing helpful constraints on the motion of the tool. Using stereo vision and tracking algorithms, the robot activates motion-scaled behavior as the tip reaches the surface, providing finer control during the critical step of engaging the membrane edge. A hard virtual fixture just below the surface limits the total downward force that can be applied. Furthermore, velocity limiting during the peeling helps the surgeon maintain a smooth, constant force while lifting and delaminating the membrane. On a phantom consisting of plastic wrap stretched across a rubber slide, we demonstrate our approach reduces maximum force by 40–70%.